2017
DOI: 10.4236/jcpt.2017.74006
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Decomposition Kinetics of Ursodeoxycholic Acid Drug Crystal

Abstract: The crystallization of ursodeoxycholic acid drug crystals in gel by reduction of solubility method is the first of its kind to be reported in literature. Monoclinic crystalline form of the structure was confirmed using single crystal X-ray diffraction analysis. This report deals with the kinetic analysis made from the thermogravimetric analysis/differential thermal analysis (TGA/DTA) data using Coats-Redfern (CR) relation. Thermodynamic parameters were also determined. Arrhenius equation for ursodeoxycholic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
(8 reference statements)
1
2
0
Order By: Relevance
“…3E). The results were consistent with previous studies that mefenamic acid was susceptible to high temperature and thermal decomposition was nonspontaneous with Gibbs free energy (∆G) of 131.01 kJ/mol [24]. These results presented that the proposed method was selective and could separate mefenamic acid from the other chemicals and degradation products.…”
Section: Forced Degradation Studiessupporting
confidence: 92%
“…3E). The results were consistent with previous studies that mefenamic acid was susceptible to high temperature and thermal decomposition was nonspontaneous with Gibbs free energy (∆G) of 131.01 kJ/mol [24]. These results presented that the proposed method was selective and could separate mefenamic acid from the other chemicals and degradation products.…”
Section: Forced Degradation Studiessupporting
confidence: 92%
“…[ 63 ] Different studies have suggested a tenfold variation in the nucleation rates due to assumption of constant Jo${J}_o$ values at normal temperature points. [ 12–64 ] Consequently, computation of Jo${J}_o$ was performed by determining Aα0.33emand0.33emEα${A}_{\alpha}\ \mathrm{and}\ {E}_{\alpha}$, using experimentally generated TGA data. A precise value of apparent activation energy false(Eαfalse)$( {{E}_\alpha } )$ of nucleation for CCPN matrix is computed by iterative procedure (Equation (16)) and provided in Table 2 and Table S2 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The following Equations [ 42 ] are presented to calculate thermodynamic parameters false(ΔH,ΔGandΔSfalse)$( {\Delta H,\ \Delta G\ {\rm and}\ \Delta S} )$, Where normalΔH$\Delta H$, normalΔG$\Delta G$ and normalΔS$\Delta S$ correspond to change in enthalpy (normalΔH$\Delta H$), change in Gibbs free energy (normalΔG$\Delta G$), and change in entropy (normalΔS$\Delta S$), respectively. normalΔHbadbreak=Eαgoodbreak−RT$$\begin{equation}\Delta H = {E}_\alpha - RT \end{equation}$$ normalΔGbadbreak=Eαgoodbreak+RTpln()kBTphA$$\begin{equation} \Delta G={E}_{\alpha}+R{T}_{p}\textit{ln}\left(\frac{{k}_{B}{T}_{p}}{\textit{hA}}\right) \end{equation}$$ normalΔSbadbreak=normalΔHnormalΔGTp$$\begin{equation}\Delta S = \frac{{\Delta H - \Delta G}}{{{T}_p}} \end{equation}$$Here, kB${k}_{B}$ is Boltzmann constant (1.38064852×0.33em1023normalJ0.16em…”
Section: Computationsmentioning
confidence: 99%